Peran Kepala Sekolah Menciptakan Kedisiplinan Lingkungan Sekolah di SMP Negeri 24 Palembang (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This study aims to determine the role of the school principal in creating discipline in the school environment at SMP Negeri 24 Palembang and to find out the supporting and inhibiting factors for the role of the principal in creating discipline in the school environment at SMP Negeri 24 Palembang. In this study, researchers used a type of qualitative research using a qualitative descriptive approach. Research data. Data collection techniques used are observation, interviews and documentation. While the techniques used in data analysis are data reduction, data presentation, data verification and drawing conclusions. Test the validity of this research data using data source triangulation and technique triangulation. The results of this study indicate that the role of the principal in creating discipline in the school environment at SMP Negeri 24 Palembang is going quite well. The results of the researchers looked at the role of the principal in creating discipline in the school environment at SMP Negeri 24 Palembang, showing indicators of the role of the principal, namely instilling, habituating, supervising, reward and punishment, guidance and motivation. The supporting factors are good inter-team cooperation and a disciplined environment. The inhibiting factor is the lack of awareness about the importance of discipline.